THE EFFECTIVENESS OF USING GIST STRATEGY IN TEACHING STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT (2022) - Nadia Salsabila, Utari (JPT : Jurnal Pendidikan Tematik, 2022)
This research is conducted on the basis of the researcher’s observatthathere the students are getting difficulties to understand the meaning of texts. The objective of the research is to find out the effectiveness of GIST strategy to teach students’ reading comprehension of narrative text. This research involved 50 students. 25 students were in the experimental class and 25 students were in the control class. The researcher used cluster random sampling to determine a sample. An instrumented test to collect the data used test. They are pre-test and post-test. The type of test is multiple choices test. The assessment of the test result was focused on students’ reading comprehension on narrative texts. Furthermore, the data was analyzed by using statistical analysis technique and the hypothesis used t-test. Based on the computation of result, the average of pre-test score of experimental class was 65.5 and the control class was 57.72. Meanwhile, the average of post- test score in the experimental class was 80.2 and the one in the control class was 72.2. So, it can be concluded that based on the result, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. The reason alternative hypothesis was accepted because the p- value (0.045) was lower than sig. α = 0.05 (5%). So, it means that there was a significance increase after applying GIST strategy on teaching students’ Reading comprehension on Narrative text